2022
DOI: 10.1111/jocd.15217
|View full text |Cite
|
Sign up to set email alerts
|

Ixekizumab treatment in patients with moderate‐to‐severe plaque psoriasis in a real‐world clinical setting

Abstract: Psoriasis is a complex, chronic, and immune-mediated inflammatory disease affecting almost 2.5% of the world population. 1 Psoriasis is primarily a dermatological condition that is most often associated with other comorbidities, including psoriatic arthritis, hypertension, diabetes mellitus, obesity, psychiatric disorders, and systemic inflammation beyond the skin. Effective, safe, and long-term management of psoriasis is important in controlling skin lesions and preventing metabolic and psychiatric comorbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Demirel Öğüt (2022) 28 Obesity/BMI Ixekizumab • Of the 7 patients who lost weight, 6 achieved impressive results (PASI75).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Demirel Öğüt (2022) 28 Obesity/BMI Ixekizumab • Of the 7 patients who lost weight, 6 achieved impressive results (PASI75).…”
Section: Resultsmentioning
confidence: 99%
“…Most of our included studies have assessed psoriasis treatment outcomes in patients with a high BMI/obesity, [25][26][27][28][29][30][32][33][34][35][36][37][38][39][40]44 which overwhelmingly highlight lower rates of achieving both PASI75 and PASI90. The majority of studies reported proportions of participants achieving PASI75, PASI90, and/or PASI100 based on BMI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations